1994
DOI: 10.1126/science.8073287
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in c-mpl-deficient mice

Abstract: Thrombopoietin (TPO) is a cytokine that is involved in the regulation of platelet production. The receptor for TPO is c-Mpl. To further investigate the role and specificity of this receptor in regulating megakaryocytopoiesis, c-mpl-deficient mice were generated by gene targeting. The c-mpl-/- mice had an 85 percent decrease in their number of platelets and megakaryocytes but had normal amounts of other hematopoietic cell types. These mice also had increased concentrations of circulating TPO. These results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
378
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 638 publications
(400 citation statements)
references
References 13 publications
18
378
2
Order By: Relevance
“…At the mature cell level, mutations in c-Mpl and Kit affect the thrombopoietic and erythropoietic lineages, respectively. 7,15,22,23 Moreover, although most other mature lineages are not affected in either single mutant, they both have deficiencies at the stem cell level. 8,[16][17][18]24 We demonstrate here, in double-mutant c-Mpl Ϫ/Ϫ Kit Wv/Wv mice, which lack both Tpo and SF receptors, that these 2 cytokine pathways contribute overlapping and nonredundant actions in mature and multipotential hematopoietic compartments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the mature cell level, mutations in c-Mpl and Kit affect the thrombopoietic and erythropoietic lineages, respectively. 7,15,22,23 Moreover, although most other mature lineages are not affected in either single mutant, they both have deficiencies at the stem cell level. 8,[16][17][18]24 We demonstrate here, in double-mutant c-Mpl Ϫ/Ϫ Kit Wv/Wv mice, which lack both Tpo and SF receptors, that these 2 cytokine pathways contribute overlapping and nonredundant actions in mature and multipotential hematopoietic compartments.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Tpo or c-Mpl knock-out mice have severe thrombocytopenia, with an 80% reduction in the number of circulating platelets. 7,22,23 c-Mpl Ϫ/Ϫ mice also have decreased numbers of clonogenic progenitor cells in multiple lineages and approximately 7-fold reduced competitive repopulation ability. 8,24 Tpo alone supports HSC survival in vitro 25,26 and acts synergistically with other early-acting factors to induce HSC division.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, homozygous TPO or c-mpl knock-out mice exhibit a profound but not lethal thrombocytopenia. 5,6 In vitro and in vivo experiments have shown that TPO is the most potent growth factor for megakaryocyte (MK) differentiation, acting on different developmental stages including MK progenitors, promegakaryoblasts and MK. 7,8 Daily TPO injection to animals including mice and primates increased platelet count up to 10-fold the control value in a few days.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups [2][3][4][5] cloned the ligand for the c-Mpl proto-oncogene [6] which is a member of the cytokine receptor superfamily. These studies and others have demonstrated that c-Mpl ligand plays a critical role in megakaryocytopoiesis and thrombopoiesis both in vitro and in vivo [2][3][4][5][7][8][9][10]. Therefore, c-Mpl ligand has been termed thrombopoietin (TPO) [3,7,8] or megakaryocyte growth and development factor (MGDF) [4].…”
Section: Introductionmentioning
confidence: 99%